On matlab finite element simulations of steady - state burger's equation - Shariffudin, Rio Hirowati (Universiti Teknologi Malaysia, 2003)
Burger's equations have been used, time and again to model successfully many physical phenomena such as in shock waves, acoustic transmision, traffic flow, supersonic flow about aerofoils and wave propagations in thermoelastic medium. Via Cole-Hopf transformation, the equations are reduced to standard diffusion equations. With the advent of modem computer technology, numerical techniques are very much sought after. Two fundamental tenets of numerical methods are the methods of finite difference and the methods using finite elements. Both methods call for the solutions of large sparse matrices. In this paper, we shall present finite element simulations of the Burger's equations using MATLAB